Imaging of tissue sections with very slow electrons - Frank, L; Nebesářová, J; Vancová, M; Paták, A; Müllerová, I (Ultramicroscopy, 2015)
The examination of thin sections of tissues with electron microscopes is an indispensable tool. Being composed of light elements, samples of living matter illuminated with electrons at the usual high energies of tens or even hundreds of kiloelectronvolts provide very low image contrasts in transmission or scanning transmission electron microscopes. Therefore, heavy metal salts are added to the specimen during preparation procedures (post-fixation with osmium tetroxide or staining). However, these procedures can modify or obscure the ultrastructural details of cells. Here we show that the energy of electrons used for the scanned transmission imaging of tissue sections can be reduced to mere hundreds or even tens of electronvolts and can produce extremely high contrast even for samples free of any metal salts. We found that when biasing a sufficiently thin tissue section sample to a high negative potential in a scanning transmission electron microscope, thereby reducing the energy of the electrons landing on the sample, and collecting the transmitted electrons with a grounded detector, we obtain a high contrast revealing structure details not enhanced by heavy atoms. Moreover, bombardment with slow electrons sensitively depolymerises the resin in which the tissue is embedded, thereby enhancing the transmitted signal with no observable loss of structure details. The use of low-energy electrons requires ultrathin sections of a thickness of less than 10nm, but their preparation is now possible. Ultralow energy STEM provides a tool enabling the observation of very thin biological samples without any staining. This method should also be advantageous for examination of 2D crystals, thin films of polymers, polymer blends, etc.
Keywords: Mice; kardiomyocyty; Biological STEM; Microscopy, Electron, Scanning Transmission; Depolymerisation; Animals; Myocytes, Cardiac; zvířata; Cathode lens; myši; Ultralow energy STEM; mikroskopie elektronová rastrovací transmisní; Tissue sections